2001
DOI: 10.1105/tpc.13.9.2021
|View full text |Cite
|
Sign up to set email alerts
|

A Vacuolar Sorting Domain May Also Influence the Way in Which Proteins Leave the Endoplasmic Reticulum

Abstract: Protein sorting to plant vacuoles is known to be dependent on a considerable variety of protein motifs recognized by a family of sorting receptors. This can involve either traffic from the endoplasmic reticulum (ER) through the Golgi apparatus or direct ER-to-vacuole transport. Barley aspartic protease (Phytepsin) was shown previously to reach the vacuole via trafficking through the Golgi apparatus. Here we show that Phytepsin normally exits the ER in a COPII-mediated manner, because the Phytepsin precursor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 26 publications
2
80
0
2
Order By: Relevance
“…Vacuolar sorting signals are grouped into three categories: sequencespecific signals, C-terminal signals, and physical structure signals (Vitale and Hinz, 2005). Three vacuolar proteins have been reported to possess physical structure vacuolar sorting signals (Saalbach et al, 1991;von Schaewen and Chrispeels, 1993;Tö rmä kangas et al, 2001). One of these, barley aspartic protease (phytepsin), was shown to reach the vacuoles through the Golgi apparatus in a coat protein complex (COP)II-mediated manner.…”
Section: Characterization Of the Plastid-targeting Signal Of Amyi-1mentioning
confidence: 99%
“…Vacuolar sorting signals are grouped into three categories: sequencespecific signals, C-terminal signals, and physical structure signals (Vitale and Hinz, 2005). Three vacuolar proteins have been reported to possess physical structure vacuolar sorting signals (Saalbach et al, 1991;von Schaewen and Chrispeels, 1993;Tö rmä kangas et al, 2001). One of these, barley aspartic protease (phytepsin), was shown to reach the vacuoles through the Golgi apparatus in a coat protein complex (COP)II-mediated manner.…”
Section: Characterization Of the Plastid-targeting Signal Of Amyi-1mentioning
confidence: 99%
“…The saposin-like plant-specific insert present in barley and soybean (Glycine max) aspartic proteinases may also function as a vacuolar sorting signal (Tormakangas et al, 2001;Simões and Faro, 2004). Additional evidence is needed to confirm the role of the saposin-like plantspecific insert in vacuolar sorting at the Golgi complex.…”
Section: The Sorting Motifs Identified In Vacuolar Proteins In Plant mentioning
confidence: 99%
“…However, it is clear that plants possess functional genes encoding the majority of the COPII machinery, as reported in yeast and mammals (Bar-Peled & Raikhel, 1997;Andreeva et al ., 1998b;Movafeghi et al ., 1999;Phillipson et al ., 2001). Biochemical studies and in vivo imaging using fluorescent protein technology have shown that over expression of Sec12, the Sar1p guanine nucleotide exchange factor (GEF) inhibits export out of the ER (Phillipson et al ., 2001;Törmäkanagas et al ., 2001;daSilva et al ., 2004), presumably by the titration of Sar1p away from putative ER exit sites. The requirement of the GTPase Sar1p for ER export has been directly demonstrated by the expression of nonfunctional mutant forms of the protein, which resulted in accumulation GFP tagged proteins in the ER which was interpreted as reflecting a block in ER export (Andreeva et al ., 2000;Takeuchi et al ., 2000;daSilva et al ., 2004).…”
Section: What Happens In Plants?mentioning
confidence: 99%
“…Proteins such as the legume globulins and legumins destined for storage vacuoles (Hillmer et al, 2001), characterised by various combinations of α, δ, and γ-TIPs ( Jiang & Rogers, 2003) are transported in noncoated Golgi-derived vesicles, which have sometimes been termed 'dense vesicles' due to the osmiophyllic nature of their contents (Hohl et al, 1996;Hinz & Herman, 2003). Classic electron microscopy and immunogold labelling has shown that sorting into these vesicles can take place as early as the cis-Golgi (see Regulation of ER to Golgi transport).…”
Section: To the Vacuolesmentioning
confidence: 99%